The effects of low and high glycemic index 24-h recovery diets on cycling time trial performance - Moore, L. J. S.; Midgley, A. W.; Vince, R.; Mcnaughton, L. R. (The Journal of Sports Medicine and Physical Fitness, 2011)
AIM: The present study investigated the effects of high and low glycemic index (GI) 24 h recovery meals on the physiological responses and subsequent athletic performance, following a glycogen depleting protocol. METHODS:Ten well trained cyclists (age, 33.6±7.4y, height, 175.3±7.6 cm, weight 74.5±8.2 kg, and VO2max, 60.5±6.0 ml/kgmin) participated in two trials in a randomized cross- over design. On day 1, subjects performed a glycogen depleting protocol after which they then consumed either high or low GI recovery diets over the next 24 h, which provided 8 g/kgBW of carbohydrate. On day 2, the subjects returned to the laboratory, 2- 3 h postprandial, to perform a 40 km time trial (TT) on the Velotron cyclePro© ergometer. RESULTS: No difference was observed in TT performance times between the high GI (93. 5±9.29 min) trial and the low GI (90.7±11.1 min) trial (t=1.1; P=0.35). Additionally, no differences in carbohydrate (F=1.1, P=0.37) fat (F=1.1, P=0.40) oxidation or blood glucose concentration (F=0.9, P=0.5) was observed. DISCUSSION:The results of the present study suggest that the ingestion of a high GI carbohydrate 24 h recovery diet following glycogen depleting exercise, has no greater effect on endurance performance than consuming a low GI carbohydrate 24 h recovery diet. It may be concluded from these results that, provided enough carbohydrate is consumed during a 24 h recovery period, there is no difference in subsequent endurance performance.